Symptomatic Meckel's Diverticulum in Pediatric Patients-Case Reports and Systematic Review of the Literature - Daniel Keese; Udo Rolle; Stefan Gfroerer; Henning Fiegel (Frontiers Media S.A., 2019)
Introduction: Our aim was to highlight the characteristics of pediatric Meckel's diverticulum with a special focus on its complications.Methods: We report a group of seven patients with Meckel's diverticulum and its resection from the Department of Pediatric Surgery between 2012 and 2017. We reviewed all patient records, clinical presentation, and intraoperative findings. The diagnosis was confirmed by surgery and pathology. For a systematic literature review, we used PubMed, Medline and Google Scholar search engines to locate articles containing terms such as Meckel's diverticulum, children, pediatric, complications and symptomatic. We included article reporting on case series in English and German on pediatric patients only.Results: All included patients (n = 7) were symptomatic. Some patients showed isolated symptoms, and others presented with a combination of symptoms that consisted of abdominal pain, bloody stool or vomiting. The median age of our seven cases was 3.5 years, including 4 male and 3 female patients. Intestinal obstruction was the most common complication; it was seen in 5 out of 7 patients (intussusception in 4 cases, volvulus in 1 case). Ectopic gastric tissue was identified in 3 cases, and inclusion of pancreatic tissue was observed in 1 case. The literature review identified 8 articles for a total of 641 patients aged between 1 day and 17 years and a male:female ratio of 2.6:1. From this group, 528 patients showed clinical symptoms related to Meckel's diverticulum. The most common symptom was abdominal pain and bloody stool. The most common surgical finding in symptomatic patients was intestinal obstruction (41%), followed by intestinal hemorrhage (34%). Complications such as perforation (10%) and diverticulitis (13%) were less frequently reported. Heterotopic tissue was confirmed on histopathology in 53% of all patients enclosing gastric, pancreatic, and both gastric and pancreatic mucosae. In one case, large intestine tissue could be found. Overall, one death was reported.Conclusion: The presented case series and literature review found similar clinical presentations and complications of Meckel's diverticulum in children. Intestinal obstruction and bleeding are more frequent than inflammation in pediatric Meckel's diverticulum. Bowel obstruction is the leading cause for complicated Meckel's diverticulum in patients younger than 12 years.